Attenuation of eccentric exercise-induced muscle damage conferred by maximal isometric contractions: a mini review - Lima, Leonardo C. R.; Denadai, Benedito S. (Frontiers in Physiology, 2015)
Although beneficial in determined contexts, eccentric exercise-induced muscle damage (EIMD) might be unwanted during training regimens, competitions and daily activities. There are a vast number of studies investigating strategies to attenuate EIMD response after damaging exercise bouts. Many of them consist of performing exercises that induce EIMD, consuming supplements or using equipment that are not accessible for most people. It appears that performing maximal isometric contractions (ISOs) 2-4 days prior to damaging bouts promotes significant attenuation of EIMD symptoms that are not related to muscle function. It has been shown that the volume of ISOs, muscle length in which they are performed, and interval between them and the damaging bout influence the magnitude of this protection. Additionally, it appears that this protection is not long-lived, lasting no longer than 4 days. Although no particular mechanisms for these adaptations were identified, professionals should consider applying this non-damaging stimulus before submitting their patients to unaccustomed exercised. However, it seems not to be the best option for athletes or relatively trained individuals. Future studies should focus on establishing if ISOs protect other populations (i.e., trained individuals) or muscle groups (i.e., knee extensors) against EIMD, as well as investigate different mechanisms for ISO-induced protection.